2020
DOI: 10.1242/dmm.041608
|View full text |Cite
|
Sign up to set email alerts
|

Diverse dystonin gene mutations cause distinct patterns of Dst isoform deficiency and phenotypic heterogeneity in D ystonia musculorum mice

Abstract: Loss-of-function mutations in dystonin (DST) can cause hereditary sensory and autonomic neuropathy type 6 (HSAN-VI) or epidermolysis bullosa simplex (EBS). Recently, DST-related diseases were recognized to be more complex than previously thought because a patient exhibited both neurological and skin manifestations, whereas others display only one or the other. A single DST locus produces at least three major DST isoforms: DST-a (neuronal isoform), DST-b (muscular isoform) and DST-e (epithelial isoform). Dyston… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…In keratinocytes, plectin and Dst-e localize to the inner plaque of hemidesmosomes and anchor keratin intermediate fibers to hemidesmosomes ( Künzli et al, 2016 ). Conditional deletion of Plec from epidermal cells causes epidermal barrier defects and skin blistering ( Ackerl et al, 2007 ), both of which is more severe than that observed in dt mice carrying Dst-e mutations ( Guo et al, 1995 ; Yoshioka et al, 2020 ). Furthermore, we recently demonstrated that conditional deletion of Dst from Schwann cells in the peripheral nervous system leads to disorganization of the myelin sheath ( Horie et al, 2020 ), similar to that observed for Plec -deficient Schwann cells ( Walko et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…In keratinocytes, plectin and Dst-e localize to the inner plaque of hemidesmosomes and anchor keratin intermediate fibers to hemidesmosomes ( Künzli et al, 2016 ). Conditional deletion of Plec from epidermal cells causes epidermal barrier defects and skin blistering ( Ackerl et al, 2007 ), both of which is more severe than that observed in dt mice carrying Dst-e mutations ( Guo et al, 1995 ; Yoshioka et al, 2020 ). Furthermore, we recently demonstrated that conditional deletion of Dst from Schwann cells in the peripheral nervous system leads to disorganization of the myelin sheath ( Horie et al, 2020 ), similar to that observed for Plec -deficient Schwann cells ( Walko et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal DST is a cytoskeletal linker protein that interacts with actin, microtubule networks and organelles. Moreover, DST has a role in endoplasmic reticulum (ER) structure and function and in autophagy in different cellular models; however, a direct link to ER-phagy has not been established [19][20][21][22][23][24][25] . DST has multiple tissue-specific isoforms , therefore, DST mutations are associated with various clinical manifestations, including dysautonomia with contractures, psychomotor retardation and motor neuropathy, but also autosomal-recessive epidermolysis bullosa simplex 26,27 .…”
Section: [H1] Epidemiologymentioning
confidence: 99%
“…[H3] Special features in the molecular diagnostics of CIP/HSAN. HSAN-causing variants affecting noncanonical alternative transcripts and isoform-specific mutations (for example WNK1 and DST gene 19,109 ) can be easily missed by routine NGS diagnostics. Similarly, structural variations including copy number variations (CNV), chromosomal rearrangements and translocations, are commonly missed by panel or exome-wide NGS approaches.…”
Section: [H2] Clinical Diagnosismentioning
confidence: 99%
“…Recessive Dst pathogenic variations in mice are responsible for dystonia musculorum ( Dst dt ), a sensory neuropathy. 89 Affected mice exhibit ataxia, autonomic disturbances, and ultimately death linked to massive degeneration of the sensory neurons in the dorsal root ganglion. The phenotype is partially rescued by restoring the dystonin-a2 expression in neuronal tissues.…”
Section: Abnormal Nerve Functionmentioning
confidence: 99%